María de Zayas and her tales of desire, death and disillusion - Greer, Margaret Rich (Icons of the Luso-Hispanic world, 2022)
"A pioneer of early modern feminism, María de Zayas y Sotomayor wrote poetry, drama and prose but is best known for two page-turning collections of short stories: Exemplary Tales of Love (1637) and Tales of Disillusion (1647). This book provides an engaging introduction to Zayas and her work. It begins by relating what we know of her life, placing her in her socio-political and economic context and addressing the issue of women's literacy. Following chapters examine her use of sexual desire, violence and humour in her tales; her narrative structures; and her oral style. The book then turns to identity construction in her tales and in society, analysing questions of gender, class, family and 'race', and to her treatment of religion, magic and the supernatural. The final chapters explore Zayas's status as a proto-feminist; her early modern reception in Spain and elsewhere; and various critical readings of her work."--